2014
DOI: 10.1007/s11524-013-9846-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Several Cancers is Higher in Urban Areas after Adjusting for Socioeconomic Status. Results from a Two-Country Population-Based Study of 18 Common Cancers

Abstract: Some studies suggest that there are urban-rural variations in cancer incidence but whether these simply reflect urban-rural socioeconomic variation is unclear. We investigated whether there were urban-rural variations in the incidence of 18 cancers, after adjusting for socioeconomic status. Cancers diagnosed between 1995 and 2007 were extracted from the population-based National Cancer Registry Ireland and Northern Ireland Cancer Registry and categorised by urban-rural status, based on population density of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 47 publications
3
65
2
1
Order By: Relevance
“…The results of adjusted analysis indicated that skin cancer was significantly related to metropolitan status. Our findings conflict with other studies that did not find a significant relationship between any defined metropolitan status and skin cancer [6,8,9,11] and those that found a significant relationship between skin cancer and living in rural versus nonrural areas [9]. The results of this study found a significant relationship between skin cancer and suburban versus rural areas as well as suburban versus urban areas.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of adjusted analysis indicated that skin cancer was significantly related to metropolitan status. Our findings conflict with other studies that did not find a significant relationship between any defined metropolitan status and skin cancer [6,8,9,11] and those that found a significant relationship between skin cancer and living in rural versus nonrural areas [9]. The results of this study found a significant relationship between skin cancer and suburban versus rural areas as well as suburban versus urban areas.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies found a positive relationship between skin cancer incidence and population density, while others did not [9]. Numerous European studies have shown individuals living in urban regions have an increased incidence of skin cancer compared to individuals living in rural regions [6,10,11]. However, a study conducted in the United States suggested metropolitan status was not significantly related to incidence of invasive cutaneous melanoma [8].…”
Section: Introductionmentioning
confidence: 99%
“…This has been found in some (Baade et al, 2011;Coory and Baade, 2005) but not all (Sharp et al, 2014;Weber et al, 2013) previous studies. Geographical differences in PCa exams could potentially be explained by area-level variations in access to health services; urban area being really dense in health services in Switzerland (Berlin et al, 2014).…”
Section: -2012 Determinants Of Pca Screeningmentioning
confidence: 48%
“…Geographical differences in PCa exams could potentially be explained by area-level variations in access to health services; urban area being really dense in health services in Switzerland (Berlin et al, 2014). Also, differences in cancer beliefs, attitudes and help-seeking behavior between urban and rural residents have been reported (Sharp et al, 2014). …”
Section: -2012 Determinants Of Pca Screeningmentioning
confidence: 99%
“…6 Other urban-rural health differences show certain cancers (stomach and lung) have a higher rate of incidence for rural inhabitants; whereas, breast cancer and heart disease are more prevalent for urbanites. 7,8 The objective of this paper is to conduct preliminary probabilistic modelling of intake for selected known (arsenic, benzene, polychlorinated biphenyls (PCBs)) or suspected (lead, tetrachloroethylene (PERC)) carcinogens, as classified by the International Agency for Research on Cancer, 9 that have been detected in North American foods, with a specific focus on differences between Canadians living in urban versus rural areas.…”
mentioning
confidence: 99%